2017
DOI: 10.1111/nph.14867
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between silica deposition and viability during the life span of sorghum silica cells

Abstract: Silica cells are specialized epidermal cells found on both surfaces of grass leaves, with almost the entire lumen filled with solid silica. The mechanism precipitating silicic acid into silica is not known. Here we investigate this process in sorghum (Sorghum bicolor) leaves. Using fluorescent confocal microscopy, we followed silica cells' ontogeny, aiming to understand the fate of vacuoles and nuclei. Correlating the confocal and scanning electron microscopy, we timed the initiation of silica deposition in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…Unless indicated otherwise, we used sorghum seedlings of about 2 weeks of age for our studies. Immature, silicifying leaves (L IS ) in our present study is analogous to leaf-2, as reported in our earlier studies (Kumar & Elbaum, 2017, 2018; Kumar et al ., 2017a). The immature leaf was cut into five equal segments.…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Unless indicated otherwise, we used sorghum seedlings of about 2 weeks of age for our studies. Immature, silicifying leaves (L IS ) in our present study is analogous to leaf-2, as reported in our earlier studies (Kumar & Elbaum, 2017, 2018; Kumar et al ., 2017a). The immature leaf was cut into five equal segments.…”
Section: Methodssupporting
confidence: 90%
“…Slp1 expression was not detected in roots where silica cells do not form. Furthermore, we could not detect Slp1 expression in mature leaf tissues, in correlation with the absence of viable, active silica cells (Kumar & Elbaum, 2018). This suggests that silica deposition in live silica cells is dependent on Slp1, while silica deposition in cell walls and possibly other locations is governed by other means such as specific cell wall polymers (Fry et al ., 2008; Law & Exley, 2011; Kido et al ., 2015; Brugiére & Exley, 2017; Kulich et al ., 2018).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…around exodermal and endodermal root cells and leaf epidermal cells; Sangster et al ., ; Gong et al ., ), and cell wall constituents, such as (hemi)cellulose, callose, pectin and lignin, have been demonstrated to interact with Si(OH) 4 as ‘templates’ or ‘scaffolding’ for silicification (Guerriero et al ., ; and references therein). Si can also polymerize in specialized cells and cellular structures of some species (particularly grasses), such as leaf silica and long cells, and spikelet hairs and papillae (Rafi et al ., ), and interesting preliminary evidence for the biological control of this process has emerged (Kumar et al ., ,b; Kumar & Elbaum, ).…”
Section: Silicon Transport In Plants: To Absorb or Not To Absorbmentioning
confidence: 99%